(untitled) (UNWE Yearbook, 2009)
The study begins with a short analysis of the fundamental reasons for the global financial and economic crisis. On this background the present status of the Bulgarian economy is described with a large number of economic, techno-economic, social, environmental and other indicators. This proves that the Bulgarian economy is among the most backward and unprepared to face the challenges of the global crisis.The study has two centers:First. The impact of the global crisis on the Bulgarian economy is investigated along 17 areas with abundant information, presented in 25 tables: the impact on the GDP growth, industry, construction, transport and communications, domestic trade, external trade, foreign direct investment, national budget, official reserve assets, gross external debt, unemployment, prices, household incomes and expenditures, income polarization, consumption, indebtedness of companies, business conjuncture, medium term budget forecast of the new government.Second. The necessity of an anticrisis programme is substantiated and its composition is submitted: major principles, urgent measures, medium-term and long-term measures. On the basis of the new Keynesian theory 35 urgent anticrisis measures are submitted for demand promotion through supporting private consumption, government consumption and infrastructure development.The study ends with conclusion.